Cohesión urbana : una naturaleza resilente a disposición de la ciudad (2018)
"In order to make a restitution of the bodies water bodies in Bogota as spaces that may be of use and enjoyment of citizenship, a strategy is proposed that understands the tunjuelo river as the most important natural water body within the urban area of Bogotá by its extension and by its natural condition. For this reason is proposed an ecosystemic revitalization of a section of the river, in order to make this as a precursor of the conformation of a continuous metropolitan ecological network, which may have the bodies of water as the main axes of said ecological structure within from the city of Bogotá. Thus, a natural infrastructure is created within the city that manages to supply the need for Bogotá's public space and that manages to give a natural space for the city that can be used for enjoyment of the citizenship, but also be of admiration and of appropriation by its users."--Tomado del Formato de Documento de Grado.